Essential Amino Acid Residues of BioY Reveal That Dimers Are the Functional S Unit of the Rhodobacter capsulatus Biotin Transporter - Kirsch, Franziska (American Society for Microbiology, 2012)
Energy-coupling factor transporters are a large group of importers for trace nutrients in prokaryotes. The in vivo oligomeric state of their substrate-specific transmembrane proteins (S units) is a matter of debate. Here we focus on the S unit BioY of Rhodobacter capsulatus, which functions as a low-affinity biotin transporter in its solitary state. To analyze whether oligomerization is a requirement for function, a tail-to-head-linked BioY dimer was constructed. Monomeric and dimeric BioY conferred comparable biotin uptake activities on recombinant Escherichia coli. Fluorophore-tagged variants of the dimer were shown by fluorescence anisotropy analysis to oligomerize in vivo. Quantitative mass spectrometry identified biotin in the purified proteins at a stoichiometry of 1:2 for the BioY monomer and 1:4 (referring to single BioY domains) for the dimer. Replacement of the conserved Asp164 (by Asn) and Lys167 (by Arg or Gln) in the monomer and in both halves of the dimer inactivated the proteins. The presence of those mutations in one half of the dimers only slightly affected biotin binding but reduced transport activity to 25% (Asp164Asn and Lys167Arg) or 75% (Lys167Gln). Our data (i) suggest that intermolecular interactions of domains from different dimers provide functionality, (ii) confirm an oligomeric architecture of BioY in living cells, and (iii) demonstrate an essential role of the last transmembrane helix in biotin recognition.